Strategi marketing dalam pengembangan medical tourism di Rumah Sakit Khusus (RSK) Bedah BIMC Siloam Nusa Dua - Swathy, I Dewa Ayu Inggra; Gorda, Anak Agung Ngurah Oka Suryadinatha (Entrepreneurship Bisnis Manajemen Akuntansi (E-BISMA), 2024)
Medical tourism is one of the tourism activities that is growing rapidly, especially in the region of Bali as an island tourist destination. This study aims to identify the marketing strategy of one of the institutions providing medical tourism services in Bali, namely BIMC Nusa Dua Hospital. This research uses a qualitative method. Data collection was carried out by in-depth interview with instruments in the form of semi-structured interview guidelines. This research involved 4 informants who were selected by purposive sampling method. The data obtained were analyzed using the Miles & Huberman data analysis method. The results showed several themes, namely medical tourism in general at BIMC Nusa Dua Hospital, the implementation of medical tourism marketing strategies, cooperation, constraints, plans, and medical tourist experience. Based on the research results, it is known that the Medical Tourism marketing strategy at BIMC Nusa Dua Hospital focuses on several aspects such as communication, product/service quality, communication, cooperation, target market, website accessibility, and evaluation and monitoring. In the future, the development of several services and capacity in cosmetic surgery services will be the focus of BIMC Nusa Dua Hospital. Promotion and patient accommodation after undergoing medical procedures need to be a concern to improve the quality of service of RS BIMC Nusa Dua.